Regional-level Indicators for Chronic Diseases of People with Disabilities: Findings from a Modified Delphi Study - Seungeun Park PhD, MPH, RN; Boyoung Jeon PhD, MPH; Young-Il Jung PhD, MPH; Juhyeon Moon MPH; So-Youn Park MD, PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Maintaining health cannot be achieved individually; it is influenced by social, legal, and institutional factors surrounding the individuals. This study aimed to identify regional-level factors that may influence the occurrence of chronic diseases among people with disabilities. To achieve this, we conducted a Delphi survey with experts to identify a set of regional indicators required for studying the health status of people with disabilities, particularly for predicting the occurrence of chronic diseases. Through the process of the Delphi survey, 24 indicators were finally selected. The major categories of the indicators were demographic factors (4 indicators), health behaviors (6 indicators), healthcare resources and utilization (11 indicators), and local community policies (3 indicators). Each category and subcategory of indicators plays a crucial role in understanding and improving the health and well-being of people with disabilities at the regional level. By addressing these factors comprehensively, policymakers and healthcare providers can develop more effective and targeted interventions, ultimately fostering a more inclusive and supportive environment for people with disabilities. The findings underscore the importance of a holistic approach to health assessment and the need for continued monitoring and evaluation to inform policy and practice.